Arabic Language and Contemporer Civilization (Capturing Arabic Language Roles in Contemporary Era) - Gustia Tahir (Universitas Islam Negeri Alauddin, 2021)
Arabic language has no doubt been regarded an international language that is often used in official meetings. Besides English, Arabic can be used as the official language in international forums. Arabic is a language that has a uniqueness in terms of grammar and Â linguistics, therefore this language is studied in many countries around the world. Arabic has an important role in current contemporary world, especially as a medium of political, economic and cultural interaction. This paper portrays the role of Arabic in the contemporary era, especially its roles in in the development of civilization.